Effects of Relay Selection Strategies on the Spectral Efficiency of Wireless Systems With Half- and Full-Duplex Nodes - Lima, Carlos H. M. de [UNESP]; Alves, Hirley; Nardelli, Pedro. H. J.; Latva-aho, Matti (Ieee-inst Electrical Electronics Engineers Inc, 2017)
This work proposes an analytical framework to study how relay selection strategies perform in half- and full-duplex deployments by combining renewal theory and stochastic geometry. Specifically, we assume that the network nodes-operating in either half-or full-duplex mode-are scattered according to a 2-D homogeneous Poisson point process to compute the relay selection cost by using a semi-Markov process. Our results show that: 1) fixed relay outperforms the reactive option in either cases; 2) the performance of both reactive and fixed relay strategies depends on the self-interference attenuation in full-duplex scenarios, evincing when they outperform the half-duplex option; and 3) the reactive relay selection suffers from selecting relays at hop basis, while the fixed relay selection benefits most from the full-duplex communication.
Keywords: Full-duplex; relay selection; renewal theory; stochastic geometry